ANALISIS NILAI-NILAI PENDIDIKAN DALAM NOVEL MENGEJAR PELANGI KARYA TRI HANDAYANI - Suhendi Syam (Lembaga Penelitian dan Pengabdian Masyarakat FKIP UMB, 2018)
Novel Mengejar Pelangi by Tri Handayani is presented in simple language but is full of meaning and educational and moral messages that provide real and real benefits for each of its readers. This novel tells the story of a karate athlete, Tri Handayani (as the main role of this novel) whose life is spent fighting against nasopharyngeal cancer. The purpose of the research is to describe the educational values contained in the novel Mengejar Pelangi by Tri Handayani. The method used in this study is a qualitative method and this type of research is a literature study. The data and data of this study used qualitative data which were stated in words or sentences, and the data in this study were in the form of words, phrases, sentences, expressions, contained in the novel Mengejar Pelangi by Tri Handayani. The results showed that the novel entitled Mengejar Pelangi by Tri Handayani, was very thick in containing educational values, namely the value of discipline 8 pieces, 3 pieces of hard work, 1 piece of curiosity, 5 pieces of social care, 1 piece of environmental care, 3 fruit, responsibility 3 pieces, reward 6 pieces achievement, and religious value as many as 22 pieces. So the educational value contained in the novel Mengejar Pelangi by Tri Handayani is 52 units. The most commonly found value is the religious value of 22 pieces.